2010
DOI: 10.1556/avet.58.2010.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A pulsed-field gel electrophoresis study of the genetic diversity of Campylobacter jejuni and Campylobacter coli in poultry flocks in Slovenia

Abstract: Campylobacter jejuni and C. coli have recently become the most frequent cause of bacterial foodborne enteric infection in most industrialised countries. Consumption and handling of undercooked contaminated poultry meat was identified as an important risk factor for human campylobacteriosis. The aim of this study was to ascertain the genetic diversity of C. jejuni and C. coli strains isolated from poultry in Slovenia. A total of 68 isolates (42 C. jejuni , 26 C. coli ) from faeces (n = 48), meat (n = 15) and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
3
1
0
Order By: Relevance
“…The results obtained through the analysis of the genetic diversity of C. jejuni indicate that the contamination of the broiler carcasses may occur during all slaughter operations, and that it is dependent on the previous colonization of the intestines of broiler. A similar observation was made by Gruntar et al [55]. This shows that the control of this microorganism will require interventions both in slaughterhouses and on broiler farms, for example, through the implementation of biosecurity programs.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The results obtained through the analysis of the genetic diversity of C. jejuni indicate that the contamination of the broiler carcasses may occur during all slaughter operations, and that it is dependent on the previous colonization of the intestines of broiler. A similar observation was made by Gruntar et al [55]. This shows that the control of this microorganism will require interventions both in slaughterhouses and on broiler farms, for example, through the implementation of biosecurity programs.…”
Section: Discussionsupporting
confidence: 79%
“…The molecular typing of the isolates from farm C by PFGE showed that all of them (28) shared the same SmaImacrorestriction pattern. Even when the digestion with KpnI endonuclease was performed, different patterns were not obtained among the isolates, a finding which was also reported in other studies [55,56]. A clonal profile among C. jejuni isolates from the same flock was also previously described [55].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…blooded animals (Gruntar et al, 2010). Worldwide, the broiler caecum has been demonstrated to be colonised to a high degree by Campylobacter species like C. jejuni (EFSA, 2016).…”
mentioning
confidence: 99%